Structure and Optical Properties of BhSe3 Thin Films Prepared by Chemical Bath Deposition Method - Musa, A. H; AL-Homrany, A.M.J (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Thin films of  BhSe3  have being deposited on glass substrates ofabout 80 - 172 Â± 14 nm thickness from an aqueous solution bath at temperature 293 K for period 0.5 to 6.0 hours  using alchemical bath deposition method .The  films  are  characterized   by  X-ray  diffraction,     X-rayflorescent techniques and optical transmittance spectra measurements in the rang 350 - 400 nm at 293 K. And shows that as deposited  films are amorphous and a  transition to polycrystalline state has taken place after  annealing  them  at  373  K,  for  30  minutes,  But  they  will  be dan1aged at 423 K, for the above period. The optical band gab of the films have been found about 1.55 to 1.50 eV as deposited time is increased from 0.5 to 6.0 hours with a  direct allowed type transition.2 ml. of hydrazine hydrate is added to the aqueous solution bath, thethickness of the deposited films is found to increase continuously with an increase in dipping period up to 6 hours and it lead to decrease  the deposition time for obtaining a sample of special thickness. Also the magnitude  of  band gap is  decrease  to 1.41-1.38  eV for  the  above periods of time.